2015
DOI: 10.13073/fpj-d-14-00003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Psychological Aspects of Wood and Laminate Products in Indoor Settings with Pictures

Abstract: Natural materials in indoor settings influence the human organism positively. Wood is a natural material and shows similar positive effects on the individual's well-being. Because of similar looks and functional properties, wood can be compared with laminate. However, when investigating psychological differences, wood is usually compared with carpets, glass, leather, stone, or plastic, but not compared with a visually similar material such as laminate. The aim of this study was to analyze and compare the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Humans perceive wood as being practical, aesthetic and climate friendly. Psychologically, wood is also considered to be warmer, more comforting, relaxing and inviting as compared to wood laminate by both expert and non-expert subjects [ 1 , 2 ]. In contrast to earlier views, newer studies have shown that wood surfaces suppress microbial activity better than plastic surfaces [ 3 ] due to their inherent antiviral, antifungal, antibacterial [ 4 , 5 ] and antistatic qualities [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Humans perceive wood as being practical, aesthetic and climate friendly. Psychologically, wood is also considered to be warmer, more comforting, relaxing and inviting as compared to wood laminate by both expert and non-expert subjects [ 1 , 2 ]. In contrast to earlier views, newer studies have shown that wood surfaces suppress microbial activity better than plastic surfaces [ 3 ] due to their inherent antiviral, antifungal, antibacterial [ 4 , 5 ] and antistatic qualities [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…To measure the psychological aspects between wood and laminate, the Quality Criteria Catalog for Green Product Evaluation (QCC-green) was used [32]. The questionnaire has 35 items which comprise 11 subscales: (1) sustainability; (2) materials and processing; (3) technical and practical function; (4) repair and maintenance; (5) perception; (6) atmosphere; (7) mobility and combinability; (8) health; (9) physical and mental stimulation; (10) performance enhancement; and (11) values and symbolic functions.…”
Section: Methodsmentioning
confidence: 99%
“…Jiménez et al [32] compared the psychological effects of wood and laminate products with photographs. Wood products are rated as significantly more warm and cozy as well as healthier and physically and mentally more stimulating than laminate products.…”
Section: Psychological Differences Between Wood and Laminatementioning
confidence: 99%
“…For example, Thompson et al (2010) Only a couple of the reviewed studies investigated wood product quality using the perceived quality approach (Costa et al, 2011;Toivonen, 2012) or examining the quality criteria (Jiménez et al, 2015(Jiménez et al, , 2016. Costa et al (2011) constructed an econometric model that explained consumers' purchase decisions by simultaneously integrating perceived product quality and tastes.…”
Section: Theory Development (T)mentioning
confidence: 99%
“…In her study, the observed dimensions of perceived product quality and value were logically linked. Jiménez et al (2015) and Jiménez et al (2016) used the quality criteria catalog for green product evaluation when investigating consumer perceptions and preferences for psychological aspects of wood products. The quality criteria catalog for green product evaluation included sustainability, health, physical and mental stimulation, performance enhancement, values, and symbolic functions, perception, atmosphere, mobility and combinability, materials and processing, technical and practical function, and repair and maintenance.…”
Section: Theory Development (T)mentioning
confidence: 99%